Analisis Kandungan Fitokimia dan Potensi Antioksidan Ekstrak Tanaman Obat Nusantara sebagai Dasar Pengembangan Sediaan Farmasi Modern dan Peningkatan Nilai Ekonomi Produk Herbal - Parwito, Parwito; Eko Sumartono (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the phytochemical composition and antioxidant potential of extracts from Indonesian medicinal plants as a foundation for developing modern pharmaceutical preparations while enhancing the economic value of herbal products. Seven local plant species, including Poikilospermum suaveolens, Curcuma longa, and Curcuma xanthorrhiza, were tested using ethanol maceration and antioxidant activity assays with the DPPH method. The results revealed variations in key bioactive compounds such as flavonoids, alkaloids, tannins, saponins, and terpenoids, with IC₅₀ values ranging from 20.44 to 80.4 µg/mL, indicating strong to very strong antioxidant activity. A negative correlation (r = –0.82) between the number of active compounds and IC₅₀ values suggests that phytochemical complexity is directly related to biological potency. From an economic perspective, plants with high antioxidant activity have strong potential as raw materials for high-value phytopharmaceuticals and natural cosmetics for export. The findings emphasize that integrating phytochemical research with a green economic approach can strengthen the competitiveness of Indonesia’s herbal industry based on sustainable natural resources.